The Development of Halal Value Chain Based on a City in Indonesia - Sochimin; Wildan, Muhammad; Dahlan, Ahmad; Aprianto, Naerul Edwin Kiky; Hamdan, Muhammad Sirajuddin Qahtan (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
This paper aims to answer the halal value chain phenomenon that is developing in several cities in Indonesia. However, the study focuses only on Purwokerto City, where the city center in Banyumas Raya has succeeded in developing various fields, including economics, education, and industry. One of the exciting things about this development is the potential of the halal value chain, especially in three main aspects: the halal food sector, halal fashion, and Islamic financial institutions. This article uses field research and qualitative descriptive analysis; the research data shows that this development has yet to become a force supported by policy, public understanding, and business actors regarding halal aspects. With a qualitative descriptive nature supported by SWOT analysis, this article provides an overview that, conceptually, Purwokerto City has tremendous and promising potential in developing the halal value chain. However, this potential is still sporadic and has not received attention from policymakers to develop Purwokerto City as a "Halal City Area" in Banyumas Raya, Indonesia.